Nazi empire : German colonialism and imperialism from Bismarck to Hitler - Baranowski, Shelley 1946- (Cambridge Univ. Press, 2011)
"Drawing on recent studies of the links between empire, colonialism, and genocide, Nazi Empire: German Imperialism and Colonialism from Bismarck to Hitler examines German history from 1871 to 1945 as an expression of the aspiration to imperialist expansion and the simultaneous fear of destruction by rivals. Acknowledging the important differences among the Second Empire, the Weimar Republic, and the Third Reich, Shelley Baranowski nonetheless reveals a common thread: the drama of German imperialist ambitions that embraced ethnic homogeneity over diversity, imperial enlargement over stasis, and "living space" as the route to the biological survival of the German Volk "--